The origin of the alpha-domain intermediate in the folding of hen lysozyme. - Matagne, A; Chung, E; Ball, L; Radford, SE; Robinson, C; Dobson, C (1998)
Stopped-flow fluorescence and circular dichroism spectroscopy have been used in conjunction with quenched-flow hydrogen exchange labelling, monitored by electrospray ionization mass spectrometry, to compare the refolding kinetics of hen egg-white lysozyme at 20 degrees C and 50 degrees C. At 50 degrees C there is clear evidence for distinct fast and slow refolding populations, as observed at 20 degrees C, although folding occurs significantly more rapidly. The folding process is, however, substantially more cooperative at the higher temperature. In particular, the transient intermediate on the major refolding pathway at 20 degrees C, having persistent native-like structure in the alpha-helical domain of the protein, is not detected by hydrogen exchange labelling at 50 degrees C. In addition, the characteristic maximum in negative ellipticity and the minimum in fluorescence intensity observed in far UV CD and intrinsic fluorescence experiments at 20 degrees C, respectively, are not seen at 50 degrees C. Addition of 2 M NaCl to the refolding buffer at 50 degrees C, however, regenerates both the hydrogen exchange and optical properties associated with the alpha-domain intermediate but has no significant effect on the overall refolding kinetics. Together with previous findings, these results indicate that non-native interactions within the alpha-domain intermediate are directly responsible for the unusual optical properties observed during refolding, and that this intermediate accumulates as a consequence of its intrinsic stability in a folding process where the formation of stable structure in the beta-domain constitutes the rate-limiting step for the majority of molecules.